Cardiovascular health trajectories and subsequent cardiovascular disease and mortality: The multi-ethnic study of atherosclerosis (MESA) - Qicong Sheng; Jie Ding; Yumin Gao; Reshmi JS Patel; Wendy S Post; Seth S Martin (Elsevier, 2023)
Objective: Longitudinal trajectories of cardiovascular health (CVH) may reflect vascular risk burden due to prolonged cumulative exposure to non-ideal CVH levels. Identifying individuals who have a higher risk CVH trajectory may facilitate treatment, screening, and prevention. We aimed to characterize 10-year trajectories of CVH and examine the associations between CVH trajectories and subsequent cardiovascular disease (CVD) and mortality. Methods: We analyzed 3674 MESA participants who completed four exams and remained CVD-free from 2000 to 2011. A 12-point CVH score was calculated based on physical activity, smoking status, body mass index, cholesterol, blood pressure, and glucose. Ideal CVH was defined as a score ≥ 9. Group-based trajectory modeling was used to identify trajectories of ideal CVH. Cox models were used to examine the association of CVH trajectories with incident CVD and death from 2011 to 2018, adjusting for age, sex, race/ethnicity, income, education, and marital status. Results: Three trajectories were identified based on the probability of achieving ideal CVH: high (n = 1251), medium (n = 760), and persistently low (n = 1663). Almost half (45.3%) of the participants had a persistently low trajectory. During a median of 7.7 years follow-up, 392 incident CVD events and 459 deaths occurred. Compared with the high CVH group, participants in the persistently low CVH trajectory group had elevated risks for CVD (adjusted hazard ratios 1.49, 95% confidence interval 1.15-1.93) and mortality (1.34, 1.06-1.70), and participants in the medium group had moderate risks for CVD (1.17, 0.86-1.59) and mortality (1.15, 0.87-1.53) (p-value for trend 0.002 for CVD, 0.014 for mortality). Conclusion: Persistently nonideal CVH is a common trajectory. Targeted prevention programs might benefit individuals with persistently nonideal CVH given their elevated risk of subsequent CVD and mortality.